First record of Aleiodes (Hemigyroneuron) (Hymenoptera: Braconidae: Rogadinae) from the Arabian Peninsula: description of new species with remarkable wing venation convergence to Gyroneuron and Gyroneuronella - Butcher, Buntika A.; Quicke, Donald L. J. (Zootaxa, 2015)
A new species of Aleiodes (Hemigyroneuron) from Saudi Arabia is described and illustrated. It represents the first species known from outside of sub-Saharan Africa, Madagascar, South East Asia and the East Palaearctic. It belongs to a species group comprising A. (H.) plurivena, glandularis and sharkeyi, but displays even more derived wing venation which is remarkably convergent with that of two distantly related rogadine genera, Gyroneuron and Gyroneuronella.